Optimised model reference adaptive control for an interacting two tank system. (1st January 2014) - Sreelatha, Preethi; Gandhi, Sanjeevi
In this paper, a method for controlling multivariable process is presented. The system under investigation is a two tank interacting process. A decoupler is designed in order to minimise the interaction effects. The model reference adaptive controller is then designed for the process with decoupler block. The tuning parameter gamma is optimised using genetic algorithm. GA optimised model reference adaptive controller was then compared with conventional controllers. The performance comparisons have been made in terms of rise time, settling time and performance criteria.